Management of horn gore injury and urticaria in a dairy cow: a case report - Abdullah, Faez Firdaus Jesse; Saharee, Abdul Aziz; Mohd Lila, Mohd Azmi; Haron, Abd Wahid; Tijjani, Abdulnasir; Muhammad, Abubakar Sadiq; Mohammed, Konto; Abba, Yusuf; Lim, Eric Teik Chung; Adamu, Lawan; Osman, Abdinasir Yusuf (Network for the Veterinarians of Bangladesh, 2015)
This paper reports how a 4-year old Friesien-Sahiwal cross cow weighing 380 kg with horn gore injury on the left labia of the vulva was managed at the Large Animal Clinic, University Putra Malaysia. The lacerated wound measuring about 4-cm long was originated as a result of horn goring from another cow two weeks prior presentation of the cow to the clinic. Physical examination of the cow incidentally revealed urticaria on the left ventro-lateral aspect of the neck suspected to be sequel of hypersensitivity. The wound was treated by topical application of a mixture of Iodine, Benacillin LA, Biomectin 1% and Ilium Dermapred made into cream. While the uticaria was treated by intramuscular injection of Chlorpheniramine maleate at 0.5 mg/kg bwt. Animal management, housing design and presence of sharp horns are some of the factors that can lead to physical traumatic injuries in dairy cows.